Human rights and reproductive health: political realities and pragmatic choices for married adolescent women living in urban slums, Bangladesh - Rashid, Sabina Faiz (© 2011 Rashid; licensee BioMed Central Ltd., 2017)
This article was published in the BMC International Health and Human Rights [ © 2011 Rashid; licensee BioMed Central Ltd. ] and the definite version is available at : http://dx.doi.org/10.1186/1472-698X-11-S3-S3 The Journal's website is at: http://bmcinthealthhumrights.biomedcentral.com/articles/10.1186/1472-698X-11-S3-S3